1996
DOI: 10.1103/physrevb.53.9123
|View full text |Cite
|
Sign up to set email alerts
|

Induced magnetization in thin epitaxial V films on Fe (100)

Abstract: Using spin-polarized secondary and Auger electron spectroscopy we find an induced magnetization in epitaxially grown V adlayers on Fe ͑100͒. Spin-dependent attenuation of the secondary electrons is quantitatively treated, following a model by Siegmann, to determine the adlayer magnetization. The first monolayer of V has a negative magnetic moment of Ϫ0.3Ϯ0.08 B per atom and thus couples antiferromagnetically to the Fe substrate. Subsequent V layers exhibit a positive magnetization. The reduction of the magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 18 publications
3
27
0
Order By: Relevance
“…Such behaviour reveals rather positive polarization of the rst atomic V interface layer and negative polarisation of the second atomic interface layer as reported in Ref. [22]. Furthermore, the observed dierent ranges and period of the AFM coupling strength across V could also depend on modication of the Fermi surface for ultrathin V(110) lms observed experimentally in Ref.…”
Section: Resultssupporting
confidence: 48%
“…Such behaviour reveals rather positive polarization of the rst atomic V interface layer and negative polarisation of the second atomic interface layer as reported in Ref. [22]. Furthermore, the observed dierent ranges and period of the AFM coupling strength across V could also depend on modication of the Fermi surface for ultrathin V(110) lms observed experimentally in Ref.…”
Section: Resultssupporting
confidence: 48%
“…Since this early calculation was restricted to FM solutions, the AF state 3 was not found for the enlarged volumes.͒ Magnetism was reported for V monolayers ͑ML͒ on magnetic and nonmagnetic substrates [4][5][6][7] and thin films on Fe͑001͒. [8][9][10][11][12][13][14] Indeed, early calculations [15][16][17] suggested that the V͑001͒ surface might also be magnetic and experimental investigation with electron capture spectroscopy by Rau et al 18 seemed to confirm these findings. But measurements of thicker V͑001͒ films on Ag ͑Ref.…”
Section: Introductionmentioning
confidence: 58%
“…Vanadium is one of those paramagnetic metals 1 that can exhibit magnetism under certain conditions (loss of coordination, hybridization with a ferromagnet), due to its large paramagnetic susceptibility 2,3 . For instance, Akoh and Tasaki 4 have reported large localized magnetic moments in hyperfine particles of V, and several experimental groups have demonstrated the existence of an induced magnetization at the V interface for V overlayers on Fe substrates [5][6][7] and Fe/V multilayers [8][9][10] . Although these trends are clear, in other aspects there has not been consensus.…”
Section: Introductionmentioning
confidence: 99%